THE PROCESS OF BASING OF ZAGATOVS DURING THE DORNALIZATION OF THE HOLES - Oqyo’lova Nigora Inobidin qizi (Bright Mind Publishing, 2025)
This article contains a variety of essays. In the dorsal of the holes involves the process of basing the taps. This process improves surface cleanliness, the quality level will be higher. When making deep holes of small diameter, it is desirable to use methods that increase high animosity and surface purity, working ability of details, as well as their rigidity in a state not less than HRC≤445. These include dornamon, flashing methods. The article uses the Dornes in a variety of processes. The state of stagnation in the plain of the forces acting on the Zagatovka Baseing the tool in an upright working walk and scheme of forces on its cone. In the process of basing we define the state of self-installation of the zagatovka.
Keywords: Dornovka, Drilling, Punches, Sinkers, Grinders, Lathes.